Initiative-taking, Improvisational Capability, and Business Model Innovation in Emerging Markets - Yangfeng Cao (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2013)
Business model innovation plays a very important role in developing competitive advantage when multinational small and medium-sized enterprises (SMEs) from developed country enter into emerging markets because of the large contextual distances or gaps between the emerging and developed economies. Many prior researches have shown that the foreign subsidiaries play important role in shaping the overall strategy of the parent company. However, little is known about how subsidiary specifically facilitates business model innovation (BMI) in emerging markets. Adopting the method of comparative and longitudinal case study, we tracked the BMI processes of four SMEs from Denmark operating in China. Using resource-based view (RBV), we develop one theoretical framework which indicates that initiative-taking and improvisational capability of subsidiary are the two primary facilitators of business model innovation in emerging markets. We find that high initiative-taking and strong improvisational capability can accelerate the business model innovation. Our research contributes to the literatures on international and strategic entrepreneurship.
hdl:10398/8814
Keywords: 330; Business model innovation; Subsidiary; Entrepreneurship; Initiative-taking; Improvisation; Tochtergesellschaft; Geschäftsmodell; KMU; Dänisch; Multinationales Unternehmen; China